Chinese International Contractors in Africa: Structure and Agency - Hong Zhang (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2021)
Do Chinese international construction and engineering contractors (ICEC) in Africa have any agency themselves, or are their strings tightly controlled by the Chinese state? Join Hong Zhang as she unpacks the role of ICECs in China's international economic relations – her findings based on primary Chinese sources may surprise you.
Keywords: 330